Highland barley ELNs and physiological responses to different concentrations of Cr (VI) stress - Ajia Sha; Bingliang Liu; Changying Liu; Qizhong Sun; Mingxing Chen; Lianxin Peng; Liang Zou; Changsong Zhao; Qiang Li (Ecotoxicology and Environmental Safety)
This study is the first to use highland barley (HB) to study the toxic effects of Cr (VI) on seedlings and the response mechanism of HELNs to Cr (VI) stress. The outcomes indicated that the germination rate of HB seeds, plant height, root length, water content, and levels of proline (PRO) and soluble sugar in both leaves and roots were all impacted by varying concentrations of Cr (VI) treatments. Differential changes in the activities of antioxidant enzymes (SOD, POD, CAT) were observed in leaves and roots of HB. We also extracted HB-derived ELNs (HELNs) and characterized and sequenced HELNs. The average particle size of CK-HELNs was 79.0 nm, and the concentration of HELNs was 4.56 E+10 (particles/mL). As the concentration of Cr (VI) increased, the particle size of HELNs in HB seedlings also increased, while the concentration decreased. A total of 29 miRNA species were identified in CK-HELNs, Cr10-HELNs, and Cr40-HELNs. Out of these, 25 were newly predicted miRNAs, and the remaining four were known miRNAs. A total of 2 known miRNAs and 11 novel miRNAs were upregulated under different concentrations of Cr (VI) stress. 1 known and 5 novel miRNAs were downregulated under different concentrations of Cr (VI) stress. Enrichment of the GO and KEGG pathways revealed that the differential gene functions were mainly focused on binding and catalytic activities. This study reveals for the first time the changes of HELNs under different concentrations of Cr (VI) stress and the toxic effects of Cr (VI) on HB seedlings. This study provides a new perspective to explore the function and utilisation of ELNs.